Influence of nanosilicon on drought tolerance in plants: An overview - Verma, Krishan K.; Song, Xiu-Peng; Singh, Munna; Huang, Hai-Rong; Bhatt, Rajan; Xu, Lin; Kumar, Vinod; Li, Yang-Rui (Frontiers in Plant Science, 2022)
Availability of insufficient water is a big challenge to plants that causes substantial losses in plant productivity and quality, followed by complete crop failure, globally. Thus, it becomes imperative to improve crop cultivation/production in unsuitable agricultural fields these days, integrating modern agri-techniques along with nanoparticles (NPs)-based approaches to extend appropriate aids to plants to deal with adverse environmental variables. Nowadays, NPs are commonly used with biological systems because of their specific physico-chemical characteristics viz., size/dimension, density, and surface properties. The foliar/soil application of nanosilicon (nSi) have shown an impact positively on plants by regulation of physiological and biochemical responses and synthesis of specific metabolites. Reactive oxygen species (ROS) are produced in plants in response to drought/water scarcity, which may enhance the ability for adaptation in plants/crops to stand with adverse surroundings. The functions of ROS influenced by nSi and water stress have been assessed widely. However, detailed information are yet to be explored about their association with plants and stress. Our review presents an update on recent developments of nSi and water stress in combination with ROS accumulation for sustainable agriculture and eco-friendly environment.